Potensi Obligasi Syariah Sebagai Sumber Pendanaan Jangka Menengah dan Panjang bagi Perusahaan di Indonesia - Sunarsih, Sunarsih (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2008)
Syariah bond is new innovation of security in islamicfinance. In this time, it has rapid growth and acceptly universal.Syariah bond is source of fund for go public firms, with theirinvestors are not for muslim investors but also for non musliminvestors. The writing main explore: what syariah bond is, itspotential source of fund for firms, threats of its developmentand solutions to eliminate the threats.